Hubungan Shift Kerja Dengan Kelelahan Kerja Pada Pekerja Bagian Daily Check di PT. Kereta Api Daerah Operasi VI Yogyakarta Dipo Kereta Api Solo Balapan - Fajar Pratiwi, Cicin, Sri Darnoto, SKM., MPH (2017)
Shift work in PT.Kereta Api Daerah Operasi VI Yogyakarta DIPO Kereta Solo Balapan often impacts associated with fatigue Subjective case of continuous result of chronic fatigue. The study was conducted to reduce the level of fatigue caused by shift work. The research method in the form of observational analytic with cross sectional method. The population in this study are all part of workers daily check as many as 72 respondents. Exhaustive Sampling Sampling with 72 respondents. Statistical test by using chi-square. From the results, p<0.000 which states there is a relationship with the work shift work fatigue on the part of workers daily check in PT.Kereta Api Daerah Operasi VI Yogyakarta DIPO Kereta Solo Balapan. Suggestions for PT.Kereta Api Daerah Operasi VI Yogyakarta DIPO Kereta Solo Balapan is expanding an existing rest area so workers can sleep to reduce fatigue and to increase the motivation of workers